Cerebrolysin enhances neurogenesis in the ischemic brain and improves functional outcome after stroke - Zhang, Chunling (2010)
Cerebrolysin is a peptide preparation mimicking the action of neurotrophic factors and has beneficial effects on neurodegenerative diseases and stroke. The present study investigated the effect of Cerebrolysin on neurogenesis in a rat model of embolic middle cerebral artery occlusion (MCAo). Treatment with Cerebrolysin at doses of 2.5 and 5 ml/kg significantly increased the number of bromodeoxyuridine positive (BrdU(+)) subventricular zone (SVZ) neural progenitor cells and doublecortin (DCX) immunoreactivity (migrating neuroblasts) in the ipsilateral SVZ and striatal ischemic boundary 28 days after stroke when the treatment was initiated 24h after stroke. The treatment also reduced TUNEL(+) cells by ~50% in the ischemic boundary. However, treatment with Cerebrolysin at a dose of 2.5 ml/kg initiated at 24 and 48h did not significantly reduce infarct volume, but substantially improved neurological outcomes measured by an array of behavioral tests 21 and 28 days after stroke. Incubation of SVZ neural progenitor cells from ischemic rats with Cerebrolysin dose dependently augmented BrdU(+) cells and increased the number of Tuj1(+) cells (a marker of immature neurons). Blockage of the PI3K/Akt pathway abolished Cerebrolysin-increased BrdU(+) cells. Moreover, Cerebrolysin treatment promoted neural progenitor cell migration. Collectively, these data indicate that Cerebrolysin treatment when initiated 24 and 48h after stroke enhances neurogenesis in the ischemic brain and improves functional outcome and that Cerebrolysin-augmented proliferation, differentiation, and migration of adult SVZ neural progenitor cells contribute to Cerebrolysin-induced neurogenesis, which may be related to improvement of neurological outcome. The PI3K/Akt pathway mediates Cerebrolysin-induced progenitor cell proliferation.